Pseudophake additive Intraokularlinsen - Hengerer, Fritz H.; Conrad-Hengerer, Ina (Augenheilkunde up2date, 2017)
Der Artikel gibt einen Überblick über die derzeit verfügbaren Implantate der Add-on-Intraokularlinsen und deren Indikationen. Auch abseits der rein refraktiven Korrekturlinsen werden Linsensysteme für Patienten mit Makulaerkrankungen vorgestellt. Darüber hinaus geht der Beitrag auf die besonderen Komplikationsmöglichkeiten der verschiedenen Techniken und Materialien ein.Implantation of artificial intraocular lenses (IOL) after cataract removal today represents the standard of care in the field of anterior segment surgery. In refractive lens exchange cases the natural lens is replaced by an IOL to correct different types of refractive situations. In the majority of the operations the refractive result is satisfying with only few deviations from target refraction.But daily practice reveals some outliers from the intended corrections with the need for further refractive enhancements, respectively. Especially odd eyes with short or long axial length, corneal astigmatism, ceratoconus or after corneal laser vision correction are more or less candidates for refractive surprises. Laser corneal surgery and additional intraocular implants are both established surgical approaches to achieve this goal in pseudophacic eyes. In paediatric cataract surgery for congenital cataracts implantation of add-on lenses can be helpful to adjust refraction according to eyeball development and prevent amblyopia.This article presents an overview about currently available implants and techniques using additional lenses to correct residual refractive errors. Furthermore, new implants for special indications like macular degeneration are addressed. A thorough evaluation of risk and benefit for each patient group and materials used are provided.
Keywords: Pseudophakie; intraokulare Refraktionskorrektur; Sulcusimplantate; multifokal; torisch